Police violence occasioning citizen complaint. An empirical analysis of time-space dynamics - Phillips, Tim (The British journal of criminology, 2000)
Violent, but non-lethal, encounters between police and civilians are an important yet neglected social problem. Even more neglected are the spatial and temporal dynamics of these events. The paper draws on Giddens's structuration theory to operationalize these variables and test their explanatory power. A multivariate analysis of data derived from citizen complaints files shows that time-space variables are important predictors of the use of major physical force by police against civilians. An explanation for this result is developed using Giddens's concept of practical consciousness. The findings of the paper suggest a need to redirect criminological and policing research towards the exploration of time-space environments